Sex Differences in Tolerability to Anti‐Programmed Cell Death Protein 1 Therapy in Patients with Metastatic Melanoma and Non‐Small Cell Lung Cancer: Are We All Equal?. (29th April 2019) - Duma, Narjust; Abdel‐Ghani, Azzouqa; Yadav, Siddhartha; Hoversten, Katherine P.; Reed, Clay T.; Sitek, Andrea N.; Enninga, Elizabeth Ann L.; Paludo, Jonas; Aguilera, Jesus Vera; Leventakos, Konstantinos; Lou, Yanyan; Kottschade, Lisa A.; et al.
Abstract: Background: Immune‐related adverse events (irAEs) have emerged as a serious clinical issue in the use of immune checkpoint inhibitors (ICIs). Risk factors for irAEs remain controversial. Therefore, we studied sex differences in irAEs in patients treated with anti‐programmed cell death protein 1 (PD‐1) therapy. Materials and Methods: All patients with metastatic melanoma and non‐small cell lung cancer (NSCLC) treated with anti‐PD‐1 therapy at Mayo Clinic Rochester and Florida from 2015 to 2018 were reviewed. Kaplan‐Meier method and log‐rank test was used for time‐to‐event analysis. Results: In 245 patients with metastatic melanoma, premenopausal women were more likely to experience irAEs (all grades) compared with postmenopausal women and men (67% vs. 60% vs. 46%), primarily because of an increase in endocrinopathies (33% vs. 12% vs. 10%, respectively). In patients with NSCLC (231 patients), women (all ages) were also more likely to develop irAEs of all grades (48% vs. 31%). Women with NSCLC were more likely to develop pneumonitis (11% vs. 4%) and endocrinopathies (14% vs. 5%). No differences in grade ≥3 toxicities were seen across sexes in both cohorts, but women were more likely to receive systemic steroids for the treatment of irAEs compared with men. Better progression‐free‐survival was observed in women with NSCLC and irAEs (10 months vs. 3.3 months) compared with women without irAEs. Conclusion: Women with metastatic melanoma and NSCLC are more likely to experience irAEs compared with men. We also observed differences between sexes in the frequency of certain irAEs. Larger studies are needed to investigate the mechanisms underlying these associations. Implications for Practice: The results of this study suggest that women may be at a higher risk for immune‐related adverse events (irAEs) compared with men when treated with anti‐programmed cell death protein 1 therapy. In addition, women were more likely to develop certain irAEs, including endocrinopathies and pneumonitis. Close follow‐up of women undergoing treatment with immune checkpoint inhibitors will allow clinicians to diagnose these treatment‐related complications early, potentially reducing their associated morbidity and mortality. In addition, a possible association between irAEs and response to therapy was observed. Abstract : This article reports on differences between men and women as related to immune‐related adverse events incidence and the potential link with response to therapy in patients with metastatic melanoma and non‐small cell lung cancer treated with anti‐PD1 agents.